Glabridin synergy with norfloxacin induces ROS in multidrug resistant Staphylococcus aureus - Pal, Anirban; Darokar, Mahendra P.; Singh, Vigyasa (Journal of general and applied microbiology, 2021)
Glabridin (Glb), a polyphenolic flavonoid inhibits the growth of MDRSA (Multidrug resistant S. aureus) 4627 by inducing ROS. Glb in combination with Norfloxacin (Nor) synergistically induced oxidative stress. Increased ROS/RNS levels, in particular, affected macromolecules' (DNA, lipid, protein) integrity and distorted cell morphology. We found correlation between drug-effects and up-/down-regulation of oxidative stress-related as well as MDR genes. These findings could considerably potentiate the dosing routine of Nor in combination with Glb, which holds a promising prospective as a antibacterial agent against S. aureus.